The capacinance absolute strain gauge - Heerens, W. Chr.; Tarasenko, Sergiy (My University, 1991)
Using the uniplanar three-terminal capacitance concept, a capacitive sensor that meets all of the demands necessary for making precision strain gauges was designed and optimized. The fundamental calculation of such a strain gauge was given. Overview of the characteristics of the capacitive sensor deformations, carried out in comparison with traditional strain gauges, showed his extraordinary advantages. It is shown, that for the first time he meets the requirements of the so-called absolute strain gauge. Suggested several possible variants of such a сonverter.
Keywords: strain gauge; тензорезистор; fundamental calculation; accuracy; reliability; фундаментальний розрахунок; точність; надійність; фундаментальный расчет; точность; надежность; кафедра електропостачання і енергоменеджменту